Development of Animation Video on YouTube Channels as an Alternative Learning Media during the Covid-19 Pandemic - Asrori; Nunuk Suryani; Nur Arifah Drajati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
Distance learning is held as an effort to continue to present the teaching and learning process for students during the COVID-19 pandemic. Many students admitted that they were not happy with the implementation of distance learning. This study aims to describe the development of Animaker application-based learning videos on the YouTube channel as an alternative to distance learning media during the covid-19 pandemic. This study uses a Design-Based Research (DBR) model. This study shows an overview of the stages of developing a learning video which includes needs analysis, material preparation and product design according to the learning objectives to be achieved, product implementation, and evaluation. Questionnaire technique is used as a method of collecting data at the stages of needs analysis and evaluation. At the needs analysis stage, the researcher gave questionnaires to 114 students who took part in learning Islamic Religious Education by distance learning or online, while at the evaluation stage, validation was carried out by two experts and the video learning trial was conducted by six students. The material expert validation in the two learning videos developed received very good and proper predicates (92% and 87%) from material experts. Meanwhile, the validation of media experts received very good and proper predicates (94% and 94%). Then, the results of student assessments in small groups showed good scores with an average score of 90% with very good and decent predicates. This indicates that the learning video developed is suitable for use as an alternative learning media during the covid-19 pandemic.